2014
DOI: 10.1177/1099636214554180
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cell micro-structure on the in-plane dynamic crushing of honeycombs with negative Poisson’s ratio

Abstract: The in-plane dynamic crushing behaviors and energy-absorbed characteristics of honeycombs with negative Poisson’s ratio (NPR) have been studied by means of explicit dynamic finite element analysis (DFEA) using ANSYS/LS-DYNA. First, the honeycomb models filled with different reentrant cells by the variation of micro-cell configuration parameters (cell-wall angle and shape ratio) are established. The respective influences of micro-structure and impact velocities on the deformation behaviors, the dynamic plateau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 37 publications
5
76
0
Order By: Relevance
“…Zhang et al [14] discussed the influences of different cell wall aspect ratios and cell-wall angles of auxetic re-entrant honeycombs, and confirmed that plateau stresses are related to impact velocities. Jin et al [15] systematically analyzed the dynamic properties and blast resistance of sandwich structure with auxetic re-entrant honeycomb cores under blast loading by using the LS-DYNA.…”
Section: Introductionmentioning
confidence: 96%
“…Zhang et al [14] discussed the influences of different cell wall aspect ratios and cell-wall angles of auxetic re-entrant honeycombs, and confirmed that plateau stresses are related to impact velocities. Jin et al [15] systematically analyzed the dynamic properties and blast resistance of sandwich structure with auxetic re-entrant honeycomb cores under blast loading by using the LS-DYNA.…”
Section: Introductionmentioning
confidence: 96%
“…Since Aluminum honeycomb has good mechanical properties, e.g. light weight, high strength, great rigidity, etc., and most studies employed it as the basic material [13,1517,26], it was used as the material of honeycomb in our study. The main parameters were gotten from these references above, which consist of the density ρ=2700 kg/m3, elastic modulus E=70 GPa, Poisson’s ratio μ=0.3 and yield strength σY=130 MPa.…”
Section: Applied Modelsmentioning
confidence: 99%
“…Researches for their potential capacities have been conducting for decades. Various enhancements in terms of compression [12], impact response, energy absorption [13], shear stiffness [14], etc. have been achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following one-dimensional (1D) shock wave theory and combining experimental and numerical simulation, prior studies start from the microstructure perspectives in order to optimize the mechanical properties and energy absorption of cellular solids via topology structure design, gradient design, hierarchy design, and negative Poisson's ratio design. [17][18][19][20][21][22][23][24][25] However, existing studies of stress wave propagation characteristics in cellular solids are limited due to the complicated microstructures, and the results primarily focus on the qualitative analysis and few assessment calculations. Symonds 26 analyzed the roles of elastic deformation in structural dynamic response, and the results indicated that elastic waves reflected energy propagation characteristics and exerted vital influences on both the deformation mode and energy absorption capacity of honeycombs.…”
Section: Introductionmentioning
confidence: 99%